Ekspresi HER2 dan Grading Histopatologis Nottingham pada Karsinoma Payudara: A Systematic Review - Firdausi, Fitri (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Breast cancer is the most common malignancy among women worldwide. Histopathological grade and HER2 status are well-established prognostic factors in invasive breast carcinoma, yet findings regarding their association remain inconsistent. This systematic review aims to summarize current evidence on the relationship between HER2 expression and histologic grade in invasive breast cancer. Methods: The review followed PRISMA 2020 guidelines. Searches were conducted in PubMed, ScienceDirect, Google Scholar, DOAJ, and Garuda using keywords related to HER2, breast cancer, and histologic grade. Eligible studies were observational research reporting HER2 status assessed by immunohistochemistry, with or without FISH confirmation, and histologic grading based on the Nottingham/Elston–Ellis system. Data extraction and risk-of-bias assessment were performed using a standardized form and the Newcastle Ottawa Scale. Results: Eleven studies met the inclusion criteria, involving more than 255,000 patients from various populations. Four studies found a significant association between HER2 positivity and high histologic grade, especially those using combined IHC–FISH testing. In contrast, seven studies mostly using IHC alone reported no significant association. Substantial heterogeneity was identified in HER2 assessment techniques, patient characteristics, and grade distribution. Overall risk of bias was moderate. Conclusion: Evidence regarding the relationship between HER2 overexpression and high histologic grade remains inconsistent. Although some studies indicate a correlation, methodological differences and population variability contribute to conflicting results. HER2 status and histologic grade should therefore be viewed as complementary, not interchangeable, prognostic markers. Further well-designed prospective studies with standardized HER2 testing protocols are needed to clarify this association.